Concepts of Normativity: Kant or Hegel? - Christian Krijnen, (Critical Studies in German Idealism ;, 2019)
The influence of Kant's understanding of morality is too strong to be ignored. Hegel, however, fundamentally criticized Kant for offering merely a 'formal' model of normativity that cannot sufficiently comprehend human action as free. Instead, Hegel argues in his doctrine of ethical life ( Sittlichkeit ) that the embeddedness of the acting subject must be taken into account when identifying normativity. Yet the issue of normativity in Kant and Hegel remains contested even today, not least due to the misunderstandings of their conceptions of the topic. The present volume explores developments within recent scholarship which enable a better understanding of the concept of normativity in the thought of Kant and Hegel.